The value relevance of esg rating: do investors care? - Setya Permana, Aryo Bimo; Gery Utomo; Panjaitan, Tuah (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This paper aims to investigate the value relevance of ESG Rating.. Using LQ45 IDX industry index, 27 firms for 2020 until 2022 period were collected as final sample. Ordinary least square regression analysis based on Ohlson price model was conducted. The result showed that ESG ratings does not have a value relevance, which means that investors particularly in Indonesian stock market still consider financial information such as profitability to make investment decision. Managerial implication such as allocating ESG resources can be useful to investor as they will consider ESG information on making investment decision.